Academic Research Related to Consumer Preferences: Comprehensive bibliometric analysis - Eva NAHALKOVA TESAROVA; Anna KRIZANOVA (Communications of International Proceedings, 2023)
The article deals with the issue of consumer preferences in today's modern world. The aim of the article is to consolidate academic research by performing a bibliometric analysis of contributions related to the topic of consumer preferences using the VosViewer visualization tool. Articles from the Web of Science database were used as input data in this analysis. Knowledge from bibliometrics and informatics has become a part not only of decision-making processes in the evaluation of research, but can also be useful for researchers themselves in their own research activities. The results of the study provide a literary and theoretical overview of the current state of consumer preferences. The article contains a graphic analysis of the number of published articles in the time horizon of the last two decades. The contribution also includes the creation and visualization of network maps showing the interconnection of keywords, countries and the most cited research publications of approximately 17,000 articles dealing with the topic of consumer preferences in various research areas/sectors.
Keywords: bibliometric analysis; consumer preferences; consumer behaviour